Teacher educators' mentoring competence-commonalities and distinctions in supporting learning to teach - Wang, Xuewei; Husu, Jukka; Toom, Auli-Mari (Elsevier, 2026)
Learning to teach during the teaching practicum is a cognitively demanding, emotionally charged, and identity-shaping process for student teachers, requiring meaningful changes that necessitate mentoring from both university-based teacher educators (UBTEs) and school-based teacher educators (SBTEs). Grounded in Transformative Learning Theory, this study examined the mentoring experiences of two groups of teacher educators in supporting learning to teach. Using a “difference-within-similarity” analytical approach, we identified nine common traits of mentoring competence (MC) across three dimensions (cognitive, social, and emotional). We revealed distinct tendencies in how UBTEs and SBTEs enact their MC. The findings not only highlight the richness and complexity of MC as a multidimensional construct, challenging the binary view that characterizes UBTEs' mentoring as theoretical and SBTEs’ as practical, but also offer practical implications for optimizing labor division and fostering more synergistic, complementary triadic mentoring.